The Role of BPD in Monitoring and Evaluation to Improve the Performance of Sihare'o Siwahili Village Government - Theozanolo Zebua, Mauritius; Ndraha, Ayler Beniah; Hulu, Fatolosa; Waruwu, Eliyunus; Maria Magdalena Bate'e (Dinasti Publisher, 2024)
This study aims to examine the role of the Village Consultative Body (BPD) in monitoring and evaluation (Monev) to improve the performance of Sihare'o Siwahili Village government. The research method used is qualitative with primary and secondary data sources. Data were collected through observation, interviews, and documentation. The results showed that the BPD has carried out the monitoring indicators well, including setting standards, measuring, and comparing. In addition, evaluation by the BPD has also been conducted, measuring the effectiveness, adequacy, and quality of village government work. However, there are several inhibiting factors faced by the BPD, such as the lack of welfare of BPD members, limited decision-making authority, and bias in the monitoring and evaluation process. Thus, this study provides a comprehensive overview of the BPD's role in M&E to improve village government performance.